Regime jurídico do risco nos contratos de concessão - Facchinatto, Renan Marcondes (2020)
The current paper addresses risk allocation in public-private partnerships taken in the broad sense (including traditional “concessions”) from the logical-semantic and legal concretism perspectives regarding interpretation of the Law in order to determine whether the matter is governed by a legal rule, as definitive conduct prescription, which could be enforced equally to all cases regardless of its particular circumstances, or by a legal principle, as a prima facie conduct prescription to be enforced via ponderation method and taking into account the specific circumstances of the specific matter at hand. This paper adopts the assumption that risk allocation is the product of an administrative decision produced via the administrative decision procedure that will enforce the regulatory provisions regarding risk allocation for a given PPP or “concession” agreement. This study adopts the analytic method based on legal dogmatic in order to determine which are the norms governing risk allocation and aims to demonstrate that in Brazilian legal system enacted by the Federal Constitution of 1988, not only legal principles should be enforced through a ponderation decision, but that legal rules can also be subject to ponderation. The core issue is to determine whether risk allocation is governed by a legal principle and thus is subject to be pondered in light of the specific facts and circumstances of any given case in order to achieve optimum balance between the interests at stake or a legal rule applicable to all cases in the same way regardless of concrete circumstances. This paper reaches its closing by presenting the mechanisms available to deal with future events taking place due to risks allocated under the theory of administrative decision